The development of a geriatric postgraduate education assessment instrument using a modified Delphi procedure - Singler, Katrin; Gordon, Adam L.; Robertson, Gillian; Roller-Wirnsberger, Regina (Oxford University Press, 2016)
There is currently wide variation in the structure and content of higher medical training in geriatric medicine across Europe and no common framework within which existing efforts can be compared. We set out to develop an audit tool to compare training between countries. An initial review of indexed and grey literature was used to develop an audit tool which was used as the basis of an Internet-based modified Delphi process incorporating the views of 14 expert geriatricians from across Europe. Items in the audit tool were included or excluded when supported by ≥75% or <50% of respondents, respectively. Items supported by 50–74% of respondents were carried forward with additional suggestions and modifications included following Round 1. Thirteen experts representing 12 countries responded to both rounds. 40/45 items were supported at Round 1. Five items were carried forward. A further 13 elements were introduced for consideration at Round 2. Consensus was gained after the second round. The final tool describes 52 items across four domains: general considerations, topics referring to knowledge in patient care, different roles that should be considered in medical training and topics regarding assessment. The resulting tool can be used as a basis for comparing higher medical training programmes in geriatric medicine between countries. Individual countries can use this to audit current practice. At an European Union level, the insights gained through such audit will form the basis of future work to develop an agreed postgraduate curriculum in the specialty.